Analyzing the Usability of University’s Websites in Sumatera Using the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) Method - Ozzy Secio Riza; Novia Lestari; Nurjanah Nurjanah (Indonesian Mechanical Electrical and Industrial Research Society (IMEIRS), 2022)
This study was carried out to analyze the quality of college websites in Sumatra in terms of usability of the website. Results of the analysis presented as ranking using TOPSIS method. The object of this study was five university websites in Sumatra, Lampung University (UNILA), Medan State University (UNIMED), Andalas University (UNAND) Padang State University (UNP), and Sriwijaya University (UNSRI) with 7 criteria including accessibility, customization and personalization, download speed, ease of use, errors, navigation, and site content. Results of the research that has been calculated then ranked using TOPSIS. The results of the research show that UNAND’s website has the most excellent usability with value similarity to the ideal solution is 0.707. Compared with webometrics’ rank released in July 2021, there is a difference in ratings. Such differences may occur because the study was measuring the usability of its website and using TOPSIS method while webometrics uses different indicators. Penelitian ini menganalisa kualitas website beberapa universitas di Sumatera ditinjau dari usability website. Hasil analisis disajikan dalam bentuk rangking dengan menggunakan metode TOPSIS. Objek penelitian ini merupakan website Perguruan Tinggi di Sumatera, yaitu Universitas Lampung (UNILA), Universitas Negeri Medan (UNIMED), Universitas Andalas (UNAND) Universitas Negeri Padang (UNP), dan Universitas Sriwijaya (UNSRI). Hasil penelitian menunjukkan bahwa website UNAND memiliki usability yang paling baik dengan nilai similarity to ideal solution adalah 0,707. Dibandingkan dengan peringkat webometrics, terdapat perbedaan peringkat. Perbedaan tersebut dapat terjadi karena penelitian mengukur usability website dan menggunakan TOPSIS, sedangkan webometrics menggunakan indikator berbeda.